2020
DOI: 10.1017/s0950268820001855
|View full text |Cite
|
Sign up to set email alerts
|

Will there be any more classical scrapie cases in sheep in Great Britain? A modelling study to predict future cases

Abstract: The aim of this study was to apply a back-calculation model to Great Britain (GB) classical scrapie surveillance data, and use this model to estimate how many more cases might be expected, and over what time frame these cases might occur. A back-calculation model was applied to scrapie surveillance data between 2005 and 2019 to estimate the annual rate of decline of classical scrapie. This rate was then extrapolated to predict the number of future cases each year going forward. The model shows that there may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Breeding programs can contribute to the reduction of prevalence of the typical form of scrapie in sheep. Arnold and Rajamyagam [ 22 ] estimated an annual reduction of 28% in scrapie prevalence cases between 2005 and 2019 in Great Britain. Hagenaars et al [ 20 ] reported a trend for reduction of scrapie prevalence in active scrapie surveillance in Netherland between the years 2002 and 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Breeding programs can contribute to the reduction of prevalence of the typical form of scrapie in sheep. Arnold and Rajamyagam [ 22 ] estimated an annual reduction of 28% in scrapie prevalence cases between 2005 and 2019 in Great Britain. Hagenaars et al [ 20 ] reported a trend for reduction of scrapie prevalence in active scrapie surveillance in Netherland between the years 2002 and 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the epidemiology techniques of spatiotemporal prediction or modeling have become effective alternatives. For example, Ancelet et al [16] applied Bayesian shared spatial component models to analyze spatial variations in the risk of scrapie infection affecting sheep in Wales (United Kingdom); Arnold and Rajanayagam [17] used a back-calculation model to predict the prevalence and trends of classical scrapie in Great Britain, which showed a possible further increase in classical scrapie cases in Great Britain. Several studies have focused on scrapie epidemic trends in European regions [17][18][19][20]; however, very little information is available on the global occurrence of prion infection and whether the ecological environment in China has an epidemic potential for scrapie.…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Organization for Animal Health (OIE), Scrapie is an infectious and notifiable disease that naturally affects both sheep and goats (Arnold & Rajanayagam, 2020;Greenwood, 2002;Konold et al, 2020).…”
Section: Introductionmentioning
confidence: 99%